Systemic cancer therapy: achievements and challenges that lie ahead - Palumbo, Michael O.; Kavan, Petr; Miller, Wilson; Panasci, Lawrence; Assouline, Sarit; Johnson, Nathalie; Cohen, Victor; Patenaude, Francois; Pollak, Michael; Jagoe, R T.; Batist, Gerald (Frontiers in Pharmacology, 2013)
In the last half of the century, advances in the systemic therapy of cancer, including chemotherapy, hormonal therapy, targeted therapy and immunotherapy have been responsible for improvements in cancer related mortality in developed countries even as the population continues to age. Although such advancements have yet to benefit all cancer types, systemic therapies have led to an improvement in overall survival in both the adjuvant and metastatic setting for many cancers. With the pressure to make therapies available as soon as possible, the side-effects of systemic therapies, in particular long-term side-effects are not very well characterized and understood. Increasingly, a number of cancer types are requiring long-term and even lifelong systemic therapy. This is true for both younger and older patients with cancer and has important implications for each subset. Younger patients have an overall greater expected life-span, and as a result may suffer a greater variety of treatment related complications in the long-term, whereas older patients may develop earlier side-effects as a result of their frailty. Because the incidence of cancer in the world will increase over the next several decades and there will be more people living with cancer, it is important to have an understanding of the potential side effects of new systemic therapies. As an introductory article, in this review series, we begin by describing some of the major advances made in systemic cancer therapy along with some of their known side-effects and we also make an attempt to describe the future of systemic cancer therapy.